Transcatheter aortic valve replacement in membranous interventricular septum aneurysm with left ventricular outflow tract extension - Banga, Sandeep (World J Cardiol, 2018)
We report a challenging case of a 81-year-old male with history of severe calcific aortic valve stenosis and aneurysmal membranous interventricular septum. The presence of anomalies in the sub-annular area can lead to valve malpositioning and its consequences. transcatheter aortic valve implantation (TAVR) in patients with aneurysm of the perimembranous interventricular septum extending into the left ventricular outflow tract has not been previously reported. This case describes a successful transfemoral TAVR with an Edwards SAPIEN XT valve (Edwards Lifesciences, Irvine, CA, United States) with such anomaly.